Component-Based Project Estimation Issues for Recursive Development - Altunel, Yusuf; Tolun, Mehmet R. (SPRINGER, PO BOX 17, 3300 AA DORDRECHT, NETHERLANDS, 2008)
In this paper we investigated the component-based specific issues that might affect project cost estimation. Component-based software development changes the style of software production. With component-based approach the software is developed as the composition of reusable software components. Each component production process must be treated as a stand-alone software project, which needs individual task of management. A typical pure component-based development can be considered as decomposition/integration activities successively applied at different levels and therefore results in recursive style of development. We analyzed and presented our results of studies on the component-based software development estimation issues from recursive point of view.